Algoritma K-Means Dan Early Warning System Pada Aplikasi Penugasan Dan Penilaian Hasil Kinerja Pegawai Berbasis Website - Maulidan, Farhan Ikhsan; Fauziah, Fauziah; Farahdinna, Frenda (STMIK Banjarbaru, 2023)
Employee performance is the key to increasing competitiveness, especially in government agencies. However, not all companies have the right media to accommodate employee performance measurement, one of which is the Ministry of Education and Culture. So far, the performance of Ministry of Education and Culture employees has been measured manually, resulting in the potential for bias and loss of data due to the fact that the recording system is still paper-based. Therefore, researchers are trying to create an application called a performance system (SIJA) which helps to increase timeliness in completing assigned tasks. This research uses the early warning system (EWS) algorithm which is used as an early detection of each employee's task completion and uses the K-Means algorithm for filtering and grouping data results to assess employee performance. The result of this research is the availability of a system that makes it easier for Finance Bureau leaders to manage the performance of their employees. Based on tests with Katalon Studio, it shows that the SIJA application received the title